DISTRIBUSI SERTA KANDUNGAN NITRAT DAN FOSFAT DI PERAIRAN DANAU RAWA PENING - Nugroho, Ary Susatyo; Tanjung, Shalihuddin Djalal; ., Boedhi Hendrarto (BIOMA, 2014)
DISTRIBUTION AND CONTENT OF NITRATE AND PHOSPHATE IN THE RAWA PENING LAKE Â ABSTRACT A research on the distribution and content of nitrate and phosphorus in water area of the Rawa Pening lake was conducted on June 5th to August 28th, 2012. The study aimed to assess the distribution area and the amount of nitrate and phosphorus in The Rawa Pening lake so that it can be seen tropics status of water area. The study is designed in the form of descriptive explorative. The study was conducted at eight stations that are determined based on the diversity of existing aquatic environmental conditions. Data collecting is done once every two months for three times. The data that was taken in the form of nitrate and phosphate content of the water. The results of the analysis showed that the distribution of nitrate and phosphate in The Rawa Pening lake is uneven. Nitrate and phosphate content vary among the research stations. Nitrate content in the water of the lake lowest average is in the Kesongo village that is 0.004 mg/L and the highest average in the Tuntang village is 0.081 mg/L. The phosphate content of the average lowest is in the Kesongo village that is 0.717 mg/L and the highest average in the village Tambakboyo is 1.350 mg/L. From the results of this study can be concluded that based on the content of nitrate, the water area of The Rawa Pening lake is oliogotrophic water area, but based phosphate content including hypertrophic water area. Keywords : distribution, content, nitrate, phosphate, The Rawa Pening lake. Â Abstrak Penelitian tentang distribusi dan kandungan nitrat dan fosfat di perairan Danau Rawa Pening telah dilakukan pada tanggal 5 Juni hingga 28 Agustus 2012. Penelitian ini bertujuan untuk mengkaji daerah persebaran serta kandungan nitrat dan fosfat di perairan Danau Rawa Pening sehingga dapat diketahui status trofik perairan tersebut. Penelitian dirancang dalam bentuk deskriptif eksploratif. Penelitian dilakukan pada delapan stasiun yang ditetapkan berdasarkan keragaman kondisi lingkungan perairan yang ada. Pengambilan data dilakukan setiap dua bulan sekali selama tiga kali. Data yang diambil meliputi kandungan nitrat dan fosfat perairan. Hasil analisis menunjukkan bahwa distribusi nitrat dan fosfat dalam perairan Danau Rawa Pening tidak merata. Kandungan nitrat dan fosfat ini sangat bervariasi antar stasiun penelitian. Kandungan nitrat dalam air danau rata-rata terendah terdapat pada desa Kesongo yaitu 0,004 mg/l dan rata-rata tertinggi pada desa Tuntang yaitu 0,081 mg/l. Adapun kandungan fosfat rata-rata terendah terdapat pada desa Kesongo yaitu 0,717 mg/l, dan rata-rata tertinggi pada desa Tambakboyo yaitu 1,350 mg/l. Dari hasil penelitian dapat disimpulkan bahwa berdasarkan kandungan nitrat, perairan Danau Rawa Pening termasuk perairan oligotrofik, akan tetapi berdasarkan kandungan fosfat termasuk perairan hipertrofik. Kata kunci : distribusi, kandungan, nitrat, fosfat, Danau Rawa Pening.